Medical genetics in China. - Bodmer, W; Clarke, C (1979)
In many areas the Chinese are considered behind the western world in their biomedical research, but they are keen to catch up, have all the contacts needed for this, and work extremely hard. Human genetics seems to have been particularly affected during the cultural revolution. This may be because they were, until recently, quite significantly affected by Lysenko. It seems likely that human genetics was a particular target, for political reasons, and also the Chinese as a whole seem most reluctant to give blood samples. Nevertheless, the efficiency of their preventive medicine shows what can be done in a disciplined country and there is no reason why genetic data should not follow the same lines.